2016
DOI: 10.1002/2211-5463.12079
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of Tim‐3 antigen on peripheral blood T cells is associated with progressive disease in osteosarcoma patients

Abstract: T‐cell immunoglobulin and mucin‐domain‐3‐containing molecule 3 (TIM‐3) plays a pivotal role in immune regulation and has been found in various tumors. However, the prevalence and distribution of Tim‐3 in osteosarcoma (OS) is still unclear. The aim of this study was to investigate the prevalence and distribution of Tim‐3 in OS. Tim‐3 on peripheral T cells from 82 OS patients and 60 healthy controls were examined by flow cytometry. Plasma levels of IL‐2, IFN‐γ, and TNF‐α were measured by ELSIA. Tim‐3 on both CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Evidence suggests that both lymphoid and myeloid lineage activation status in both the local and systemic immune environments may carry clinically useful information regarding osteosarcoma disease progression, metastasis, and survival [16, 17, 46]. However, once the primary tumor is removed, it can no longer provide up-to-date information on the evolving antitumor immune response.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that both lymphoid and myeloid lineage activation status in both the local and systemic immune environments may carry clinically useful information regarding osteosarcoma disease progression, metastasis, and survival [16, 17, 46]. However, once the primary tumor is removed, it can no longer provide up-to-date information on the evolving antitumor immune response.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Shang et al (19), TIM-3 expression resulted in tumor cells acquiring features associated with aggressive epithelial-mesenchymal transition and thus may be involved in the pathogenesis of osteosarcoma (19). A recent study revealed that aberrant expression of the TIM-3 antigen on peripheral blood T cells is associated with progressive disease in patients with osteosarcoma, and TIM-3 may be a possible diagnostic biomarker of osteosarcoma and/or a prognostic biomarker of osteosarcoma progression (20).…”
Section: Discussionmentioning
confidence: 99%
“…A third inhibitory receptor on T cells, Tim-3, was also analysed given its emerging role as an inhibitor of T cell function and anti-tumour immunity[ 31 ]. Elevated levels of Tim-3 on T cells from osteosarcoma patients have been associated with poor survival while Tim-3 + PD-1 + tumour-specific T cells in melanoma were found to be dysfunctional [ 18 , 32 ]. Blocking antibodies against Tim-3 have been shown to promote anti-tumour immunity both as sole agents and in combination with other treatments and antibodies against additional inhibitory receptors [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%